(untitled) (Journal of Engineering, 2003)
in the modern field of heavy ion atomic physics, determined through Lorentz transformation [W. Greiner 1997]. At high energies one must investigate the relative wave equations. This means equations, which are invariant under Lorenz transformation. The Lorentz transformation is so important, that it needs, to be derived on a more logical basis. Many textbooks and research papers have derived Lorentz transformation by different postulates [Anderson, J.L. 1967][G. Nadean 1962][H.A. Atwater 1974], which are not treated electro-dynamically this paper exhibits a method of finding the Lorentz transformation by exploiting the Maxwell’s famous equations of the electromagnetic field equations